2010
DOI: 10.4070/kcj.2010.40.3.125
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Function in Children and Adolescents With Type 1 Diabetes Mellitus

Abstract: Background and ObjectivesAdult studies have reported that patients with diabetes mellitus (DM) show ultrastructural and functional myocardial deterioration. The aim of this study was to assess whether cardiac functional deterioration can be detected in pediatric patients with type I DM and whether or not a relatively short duration of DM and hyperglycemia influences cardiac function.Subjects and MethodsForty-seven children and adolescents with DM and 38 healthy subjects (control group) were enrolled. Glycosyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
2
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 20 publications
5
27
2
4
Order By: Relevance
“…However, in our results, we could find no correlation between HbA1C and decreased GLS. These findings don't agree with studies demonstrating a relationship between glycemic control and cardiac function in diabetic children [14]. They found that a higher mean HbA1c was significantly associated with changes in LV structure and function in patients with T1D.…”
Section: Discussioncontrasting
confidence: 57%
“…However, in our results, we could find no correlation between HbA1C and decreased GLS. These findings don't agree with studies demonstrating a relationship between glycemic control and cardiac function in diabetic children [14]. They found that a higher mean HbA1c was significantly associated with changes in LV structure and function in patients with T1D.…”
Section: Discussioncontrasting
confidence: 57%
“…Studies on adults have reported that patients with T1D show ultra-structural and functional myocardial deterioration 3). Similarly, it has been reported that young patients with T1D have significant changes in left ventricular dimension and myocardial relaxation 4).…”
Section: Introductionmentioning
confidence: 95%
“…However, we calculated mean HbA1c levels in patients, whereas in other studies, only the level of HbA1c at the time of study was considered. 18,30,34 To date, there is only one other study showing the relationship between ADMA levels and echocardiographic parameters in childhood T1DM. Abd El Dayem et al 20 not only found a negative relationship between NO levels and echocardiographic parameters but also showed that the most important indicator of NO levels is ADMA concentration.…”
Section: Discussionmentioning
confidence: 99%